Soft Power Strategy in Improving Saudi Arabia’s Global Image Through The Sportswashing Program - Muda Maestro Junior; Gonda Yumitro; Muhammad Subhan Setowara (PERSPEKTIF, 2026)
This study analyses Saudi Arabia’s soft power strategy through sportswashing as an instrument of public diplomacy aimed at enhancing its global image and strengthening its international economic position within the framework of Vision 2030. A qualitative descriptive approach is employed, using content analysis of academic literature, official government documents, and reports from international organizations to examine how sportswashing functions across multiple strategic registers systematically. The findings reveal that Saudi Arabia’s sportswashing strategy operates across three interconnected dimensions: reputational, economic, and normative. In the reputational dimension, sport is used to reconstruct the country’s global image and redirect international attention from documented human rights violations. In the economic dimension, sportswashing drives diversification through tourism growth, large-scale sports investment, and expansion of the services sector. In the normative dimension, sport constructs a new social identity aligned with global values of modernity and inclusiveness, though reforms remain largely symbolic without substantive institutional change. Overall, sportswashing provides significant strategic benefits; however, long-term sustainability depends critically on the credibility of genuine domestic reforms that can substantiate Saudi Arabia’s moral legitimacy internationally. This study contributes to soft power and public diplomacy scholarship by offering an integrated analytical framework demonstrating how sportswashing operates simultaneously across reputational, economic, and normative dimensions as a tool of authoritarian legitimacy management